(untitled) (CIPEEX, 2024)
THIS TEXT DISCUSSES THE NOTION OF SCHOOL SPECIFICITY, IN OTHER WORDS, WHAT ARE SCHOOLS FOR?. IN THIS SENSE, THE STUDY IS BASED ON BIBLIOGRAPHIC RESEARCH, CONSIDERING THE REFLECTIONS OF CONTEMPORARY AUTHORS ABOUT THE PROBLEMATIZATION IN QUESTION. IN SUMMARY, IT IS PROPOSED TO REFLECT ON THE SPECIFICITY OF THE SCHOOL, THE ELEMENTS THAT CONSTITUTE ITS CREATION AND ON THE IMPORTANCE OF (STILL) BELIEVING IN WHAT ONLY A SCHOOL IS CAPABLE OF DOING AND HAVING AN IMPACT. THIS IS DONE WITH THE AIM OF CONSOLIDATING REFLECTIONS ON THE IMPORTANCE OF SCHOOL FOR THE CONSTITUTION OF A COMMON HUMAN WORLD, MORE HARMONIOUS, ETHICAL AND RESPONSIBLE, WHICH WELCOMES THE GENERATIONS THAT ARRIVE HERE. THEREFORE, IT IS THE SPECIFICITY OF THE SCHOOL TO OFFER THE NEW GENERATIONS ALL THAT THEY MUST LEARN SO THAT THEY CAN FIND THEIR PLACE IN THE COMMON HUMAN WORLD. AND FOR THIS TO HAPPEN, IT IS NECESSARY THAT THE RESPONSIBILITY OF THE SCHOOL FOR THE NEW GENERATIONS AND FOR KNOWLEDGE BE TAKEN SERIOUSLY. SCHOOLS SERVE, THEREFORE, TO ALLOW THE UNIVERSALIZATION OF VARIOUS EXPLANATIONS. THE SPECIFICITY OF THE SCHOOL IS RELATED TO KNOWLEDGE AND THE CAPACITY FOR THE GOOD OF KNOWLEDGE, THIS MEANS THAT IT IS A PLACE FOR STUDY, ACTIVITIES AND EXERCISES. IT IS A PLACE WHERE THE THINGS OF THE WORLD CAN BE SHARED PUBLICLY WITH THE NEW GENERATIONS. SCHOOLS INITIATE THE YOUNGEST IN SYMBOLIC INHERITANCES CAPABLE OF GIVING INTELLIGIBILITY TO THE HUMAN EXPERIENCE AND DURABILITY TO THE COMMON WORLD. THIS IS WHAT THEY ARE FOR: TO TRANSMIT THIS POWERFUL KNOWLEDGE, WHICH IS ABLE TO EXPAND THE INDIVIDUAL KNOWLEDGE OF THE STUDENT FROM WHAT HE DOES NOT YET KNOW.